Three-dimensional hierarchical GeSe2 nanostructures for high performance flexible all-solid-state supercapacitors - Wang, Xianfu (Advanced materials (Deerfield Beach, Fla.), 2013)
Copyright © 2013 WILEY-VCH Verlag GmbH & Co. KGaA, Weinheim.